'People Just Need to Try It to Be Converted!': A Picture of Consumer Mental Health Research in Australia and New Zealand. (11th August 2020) - Scholz, Brett; Happell, Brenda; Gordon, Sarah; Warner, Terri; Roper, Cath; Ellis, Pete; Waks, Shifra; Platania-Phung, Chris
Abstract: A range of barriers that impede collaborations between consumer researchers and other researchers have been identified, despite clear acknowledgement of the benefits of this approach in the literature. Recent research has questioned whether the costs of collaborative research outweigh the benefits. The overarching aim of the current study is to better understand non-consumer researchers' attitudes to, and issues concerning, engagement with consumer researchers. Non-consumer researchers from mental health disciplines were invited to participate in the cross-sectional Consumers as Researchers in Mental Health survey, and to respond to open-ended questions about their experiences of collaborative research with consumer researchers. The findings demonstrate a range of benefits associated with collaborations with consumer researchers – including increased relevance and credibility of research, and greater translation of research findings into changes in health policy, service, research and education. Collaborations were found to be varied and not limited by research design, decision-making styles, or research topic. Understanding these benefits within the context of identified barriers can make an important contribution to the proliferation of mental health consumer researcher roles.